Larwy sprężykowatych (Elateridae) występujące w próchnie brzóz (Betula spp.) na terenie Kampinoskiego Parku Narodowego - Perliński, Stanisław; Sawoniewicz, Michał (Leśne Prace Badawcze, 2011)
The aim of this paper was to study the taxonomic composition and structure of assemblages as well as the seasonal biomass dynamic of the wireworms living in decaying wood of birch in the Kampinos NP. Studies were conducted over a 12 month period. To collect wireworms, samples of wood mould were taken from 10 different forest habitats. Samples were collected and then described according to their characteristics, i.e. form of wood mould, phase of wood decomposition, shading, humidity, rot colour and diameter. The wireworms were sampled from wood mould with the use of photoeclectors. As a result, 970 specimens of wireworms representing 8 taxa were collected, of total biomass 6.7082 g. The vast majority of saproxylobiontic wireworms came from the genus Ampedus (93.1%), with the minor exceptions of: M. villosus (1.4%) and D. linearis (1.2%). Most taxa occurred in the following habitat types: fresh deciduous forest, alder forest, wet coniferous forest and fresh mixed coniferous forest, whilst there were also a few in wet mixed coniferous forest. The biomass and abundance of wireworms were highest in deciduous forest habitats and lowest in coniferous habitats. Wireworms were most abundant in June (15.8%) and July (19.3%) as a result of their body size and mobility, and next in October (9.8%) because of their migration to wood moulds for over-wintering. Fallen tree trunks are the most inhabited form of wood mould – 7 taxa; followed by standing trunks and stumps – with 4 taxa each, and finally tree holes and lateral dead wood – 1 taxon. The highest biomass of soil and saproxylic wireworms per one sample was recorded in the phase IV (0.0209 g), next in the phase III (0.0190 g), and the lowest one in the phase II (0.0157 g). Humid wood mould, is the preferred food for wireworms, however this is not so important for phytophages eating live plants. For thermophilous and zoophagous wireworms living in the soil and feeding on live animals, dry wood mould is preferred. The occurrence of wireworms in the forest ecosystems depends chiefly on habitat and wood mould diversity in both its quality and quantity.